Acolhimento a imigrantes no centro especializado em reabilitação - cer iv de Foz do Iguaçu: limites e possibilidades - Buytendorp, Lauriane Alle (2022)
Foz do Iguaçu has become a strategic point to attract people from other locations due to its geographic position, economy and tourist attractions, very much related to the fact that it is a municipality with a triple border. Access to health, diagnoses, treatments and rehabilitation are common demands that are on the rise, depending on the location, especially by immigrants. Access to the rehabilitation service is related to welcoming and responses to the needs of the people assisted. In this sense, the present research has the general objective of identifying some limits and possibilities encountered by professionals through the reception of immigrants with disabilities, assisted by the Specialized Rehabilitation Center Dr. José Carlos Azeredo – CER IV, in the municipality of Foz do Iguaçu – PR. As for the methodology, we opted for research with a qualitative approach of an exploratory nature. Eighteen professionals linked to the process of physical, auditory, intellectual and visual rehabilitation of CER IV participated in the study. As a technique, we opted for the individual, semi-structured interview, with eleven guiding questions. Data analysis indicates that professionals working in different areas of rehabilitation mostly have difficulty communicating with the patient in an immigration situation, which impacts on the reception and execution of the singular therapeutic plan, especially due to the fact that both professionals and patients immigrants, commonly speak and understand only the mother tongue. The research also pointed out the scarcity of dialogues, policies and training that may effectivelycontribute to a more humanized service within the theme in question.